ANALISIS LINGUISTIK FORENSIK TERHADAP PROFILING TEDDY MINAHASA DALAM KASUS NARKOTIKA - Zaqia Nur Anisa; Irwan Suswandi (Universitas Negeri Makassar, 2025)
This study aims to analyse the dialect, idiolect, and register in Teddy Minahasa's speech using a forensic linguistic approach. William Labov's theory of language variation is used to identify an individual's geographical and social background through their language style. The method used is qualitative with data collection techniques based on observation, including free observation and note-taking techniques. The results show that Teddy Minahasa's dialect is similar to the Manado dialect, as seen in the omission of the vowel in the word ‘saya’ to “sa” and the pronunciation of the vowel /a/ which is more open. His idiolect is evident in his habit of using the word ‘ya’ at the beginning, middle, or end of a sentence as a marker of emphasis and validation of his statements. The register shows a semi-formal style, with a mixture of formal diction such as ‘bapak’ (sir) and ‘saya’ (I) and non-formal diction such as ‘ga’ (you), “kok” (why), and ‘suka-suka’ (as I like), indicating an adjustment to a more open communication context. The long, orderly, and complex sentence structure also reflects his background as a member of the police force.